Learn Java for Android development : migrating Java se programming skills to mobile development - Späth, Peter (Apress, 2020)
Gain the essential Java language skills necessary for using the Android SDK platform to build Java-based Android apps. This book includes the latest Java SE releases that Android supports, and is geared towards the Android SDK version 10. It includes new content including JSON documents, functional programming, and lambdas as well as other language features important for migrating Java skills to Android development. Android is still the world's most popular mobile platform and because this technology is still mostly based on Java, you should first obtain a solid grasp of the Java language and its APIs in order to improve your chances of succeeding as an effective Android apps developer. Learn Java for Android Development, 4th Edition helps you do that. Each of the book's chapters provides an exercise section that gives you the opportunity to reinforce your understanding of the chapter's material. Answers to the book's more than 500 exercises are provided in an appendix. Once you finish, you will be ready to begin your Android app development journey using Java. What You Will Learn Discover the latest Java programming language features relevant to Android SDK development Apply inheritance, polymorphism, and interfaces to Android development Use Java collections, concurrency, I/O, networks, persistence, functional programming, and data access in Android apps Parse, create, and transform XML and JSON documents Migrate your Java skills for mobile development using the Android platform Who This Book Is For Programmers with at least some prior Java programming experience looking to get into mobile Java development with the Android platform.